IMPLEMENTASI VARIASI ANATOMI DAUN PANGKAL DAN PUCUK TANAMAN HIAS DIKOTIL DALAM MEDIA ATLAS - Permatasari, Intan; Daningsih, Entin; Mardiyyaningsih, Asriah Nurdini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Media atlas containing morphological and anatomical descriptions of the leaves of the six ornamental plant species dicotyledon at the base and shoots is used as a learning medium to facilitate students in understanding the material structure and function of class XI plant tissues. This study aims to compile and validate media atlases of leaf morphology and anatomy of six types of dicot ornamental plants. Research using descriptive quantitative methods. Atlas media is made through pre-production, production, and post-production stages. The media atlas validation instrument is an instrument questionnaire and a media validation questionnaire which consists of four aspects with 21 statement items. The media instrument was validated by 2 FKIP lecturers and the media questionnaire was validated by 5 validators (2 FKIP UNTAN lecturers and 3 high school class XI teachers) using a Likert scale. Media validation calculations refer to Lawshe. The results of the instrument validation show that the media validation sheet is feasible to use, which means that it can be used by the validator to assess learning media. The results of the media validation analysis obtained a VCI value of 0.98 from the 4 aspects assessed. Aspects of presentation, language, and use have reached a minimum score but the content aspect has only reached 0.94 so that it still requires improvement in the content aspect before being tested in learning.